The Genetic Diversity of Hippophae rhamnoides in Technogenic Areas of Northern Kazakhstan - Shadmanova, L.; Kulboldin, T.; Token, A.; Kanapin, Ch.; Akhatov, K.; Mukan, G.; Yeszhanova, A.; Razhanov, M. (Fundamental and Experimental Biology, 2025)
Genetic diversity is a key indicator of a species’ evolutionary development, adaptability to environmental changes, and long-term survival. Globally, the sustainable use and conservation of genetic resources, including in situ protection and population-level genetic studies, is a major scientific priority. Sea buckthorn (Hippophae rhamnoides L., Elaeagnaceae) has been traditionally used for centuries, but only recently recognized for its significant economic value. Its berries are rich in biologically active compounds, making the species increasingly important in medicine, agriculture, food, and cosmetics across Europe and Asia. This study evaluates the genetic diversity of Hippophae rhamnoides in technogenic zones of Northern Kazakhstan using ISSR markers. Seed samples were collected from two plant populations in the Prigorodny Forest District, Kostanay region, for molecular analysis. ISSR analysis showed high within-population polymorphism (87%) and lower between-population polymorphism (13%) in Hippophae rhamnoides. UPGMA clustering revealed genetic differentiation between and within populations, indicating distinct genetic origins and potential cross-pollination. The high within-population polymorphism and clustering pattern indicate genetic differentiation of Hippophae rhamnoides forms according to their origin. This study is preliminary, and further research should include populations from other technogenically affected regions and comparative analysis with populations from protected areas.